Scaling financial and information services for smallholder adaptation: Project launch in Zambia - Gamoyo, Majambo; Slane, David; Ghosh, Aniruddha (2025)
On 13–14 October 2025, partners and stakeholders met in Lusaka, Zambia, for the inception workshop of the Scaling Financial and Information Services for Smallholder Adaptation Project. The event marked the launch of a two-year initiative to strengthen smallholder farmers’ resilience to climate shocks by improving their access to financial and information services.